Comparison of De Ritis Ratio and other systemic inflammatory parameters for the prediction of prognosis of patients with transitional cell bladder cancer. Issue 4 (1st November 2020) - Batur, Ali Furkan; Aydogan, Muhammed Furkan; Kilic, Ozcan; Korez, Muslu Kazım; Gul, Murat; Kaynar, Mehmet; Goktas, Serdar; Akand, Murat
Abstract: Objective: To investigate the clinical value of preoperative De Ritis ratio (aspartate aminotransferase/alanine aminotransferase) (DRR) in patients with transitional cell bladder cancer (TCBC) at initial diagnosis. The secondary objective was to investigate the status of systemic inflammatory parameters, such as neutrophil‐lymphocyte ratio (NLR), lymphocyte‐monocyte ratio (LMR), platelet‐lymphocyte ratio (PLR) and platelet‐monocyte ratio (PMR). Materials and Methods: The records of patients with primary TCBC who underwent transurethral resection were retrospectively evaluated. The relationship of DRR and systemic inflammatory parameters with clinicopathological findings, recurrence and progression status was evaluated separately. Results: There was no significant difference in the DRR according to the clinicopathological findings, recurrence and progression. Significant differences were found between the NLR and the patient groups for tumour diameter, tumour stage, tumour grade and progression. In univariate analysis, the LMR was found to be associated with progression, and also the PLR and LMR were found to be associated with recurrence. Decrease in LMR and increase in LMR score demonstrated by multiple analysis was shown as independent predictors of progression and recurrence development. Conclusions: This paper shows a positive correlation between poor prognosis in TCBC and the systemic inflammatory markers, namely NLR, LMR, PLR and PMR, but not DRR.